Question about SoftMath Algebrator - Algebra Homework Solver (689076614429)

Hello,**I will show you the steps. You should be able to carry them out.**

1. Get rid of the 5 on the left by transferring it to the right, while obeying the rules.

2. Write the right side as a fraction with 16 as denominator.

3. Calculate 4^3.

4. Get rid of the number that multiply x by transferring to the right side, while obeying the rules.

5.Express the right hand side as a fraction reduced to its simplest form (Hint:a factor 16 will simplify).

6. Give the result as fraction or calculate its decimal value if that is what is asked.

Hope it helps.

Posted on Sep 21, 2009

Hi,

a 6ya expert can help you resolve that issue over the phone in a minute or two.

best thing about this new service is that you are never placed on hold and get to talk to real repairmen in the US.

the service is completely free and covers almost anything you can think of (from cars to computers, handyman, and even drones).

click here to download the app (for users in the US for now) and get all the help you need.

goodluck!

Posted on Jan 02, 2017

5x (-3x) = 2x -3x - -3x = 0

The equation then becomes 2x=10 2x/2 = x and 10/2 =5

then x=5. does it work 5x5=10+3*5 YES

The equation then becomes 2x=10 2x/2 = x and 10/2 =5

then x=5. does it work 5x5=10+3*5 YES

Jan 20, 2017 | The Office Equipment & Supplies

TDC should put piston 1 to its highest position with valves closed (compression). 5.16 BTDC if you don't have the markings on the flywheel and the engine block, you should make them anywhere and use them as reference markings. Hope it helps.

Oct 15, 2014 | Enfield Motorcycles

Type **solve(log(x^5,16)-log(125,64)+log(x^(1/2),4),x,0.5**

Its equation with guess 0,5. Then press enter and you will give result

x=5^(1/3)=1.70997

Or, you can use equation solver with eqn=0(MATH, then B option)

See captured images below

x=5^(1/3)=1.70997

Or, you can use equation solver with eqn=0(MATH, then B option)

See captured images below

Feb 26, 2013 | Texas Instruments TI-83 Plus Calculator

4X+3-3=3X-4-3=3X-7

4X=3X-7

4X-3X=3X-3X-7

X=-7

The answer is X=-7

4X=3X-7

4X-3X=3X-3X-7

X=-7

The answer is X=-7

Dec 06, 2011 | Knowledge Adventure Math Blaster...

For 3x(7x+6x)=0, x=0

For 3x(7x+6x)=1, x=1/39

For 3x(7x+6x)=2, x=2/39

For 3x(7x+6x)=3, x=3/39 or 1/13

For 3x(7x+6x)=4, x=4/39

And so on...

For 3x(7x+6x)=1, x=1/39

For 3x(7x+6x)=2, x=2/39

For 3x(7x+6x)=3, x=3/39 or 1/13

For 3x(7x+6x)=4, x=4/39

And so on...

Jun 22, 2011 | Acer Aspire One Netbook

5x -2(x-2) = 6 -2(-3x-3)

5x -2x +4 = 6 +6x +6 (use the distributive property)

3x + 4 = 6x + 12 (collect terms)

4 = 3x + 12 (subtract 3x from both sides to get all x on one side)

-8 = 3x (subtract 12 from both sides to get only x on one side)

-8/3 = x (divide both sides by 3 to get x by itself)

Check

5(-8/3) -2((-8/3)-2) = 6 - 2(-3(-8/3)-3)

-40/3 -2(-8/3-6/3) = 6 - 2(8-3)

-40/3 -2(-14/3) = 6 -2(5)

-40/3 + 28/3 = 6 - 10

-12/3 = -4 (yes)

5x -2x +4 = 6 +6x +6 (use the distributive property)

3x + 4 = 6x + 12 (collect terms)

4 = 3x + 12 (subtract 3x from both sides to get all x on one side)

-8 = 3x (subtract 12 from both sides to get only x on one side)

-8/3 = x (divide both sides by 3 to get x by itself)

Check

5(-8/3) -2((-8/3)-2) = 6 - 2(-3(-8/3)-3)

-40/3 -2(-8/3-6/3) = 6 - 2(8-3)

-40/3 -2(-14/3) = 6 -2(5)

-40/3 + 28/3 = 6 - 10

-12/3 = -4 (yes)

Dec 19, 2010 | Answer Racing Ion Motorcycle Jersey 2010

(2x - 3y)(3x + 2y) = 2x*3x + 2x*2y - 3y*3x - 3y*2y

= 6x^2 + 4xy - 9xy - 6y^2

= 6x^2 - 5xy - 6y^2 You multiply each element in the first set of brackets by each element in the second set of brackets and then consolidate like terms and arrange them in sequence of powers, first x and then y. So:

2x by 3x = 6x squared

2x by 2y = 4xy

-3y by 3x = -9xy

-3y by 2y = 6y squared

6x squared -5xy + 6y squared

= 6x^2 + 4xy - 9xy - 6y^2

= 6x^2 - 5xy - 6y^2 You multiply each element in the first set of brackets by each element in the second set of brackets and then consolidate like terms and arrange them in sequence of powers, first x and then y. So:

2x by 3x = 6x squared

2x by 2y = 4xy

-3y by 3x = -9xy

-3y by 2y = 6y squared

6x squared -5xy + 6y squared

Dec 04, 2010 | Yahoo Computers & Internet

Here you are :

2X2-3x+5=0 => 4-3x+5=0; (2X2=4) => -3x+9=0; (4+5=9) => 9 = 3x; (-3x moved to the right-hand side and it became 3x) => 9/3=x; (3 moved to the right hand side, so it becomes 1/3, i.e 1/3X9= 9/3) i.e. x=9/3 => x=3

Hence x equals to 3.

You can add or remove the explanation/description, I simply add them to make you understand.

If you need help, let me know.

Good luck.

Thanks for using** FixYa.**

2X2-3x+5=0 => 4-3x+5=0; (2X2=4) => -3x+9=0; (4+5=9) => 9 = 3x; (-3x moved to the right-hand side and it became 3x) => 9/3=x; (3 moved to the right hand side, so it becomes 1/3, i.e 1/3X9= 9/3) i.e. x=9/3 => x=3

Hence x equals to 3.

You can add or remove the explanation/description, I simply add them to make you understand.

If you need help, let me know.

Good luck.

Thanks for using

Oct 08, 2010 | Computers & Internet

[3(x-5)-4(-3x+2)]-[4(6-x)]

[(3x-15)-(12x+8)]-(24-4x)

(-9x-23)-(24-4x)

-13x-(-1)

this is 9th grade stuff.

[(3x-15)-(12x+8)]-(24-4x)

(-9x-23)-(24-4x)

-13x-(-1)

this is 9th grade stuff.

Sep 13, 2008 | Texas Instruments TI-84 Plus Calculator

B. 2((2-Y)/3)-Y=3

2(2-Y)-Y=9

4-2Y-Y=9

-3Y=9-4

-3Y=5

-Y=5/3

Y=-1.67

A. 3X+(-1.67)=2

3X-1.67=2

3X=2+1.67

3X=3.67

X=3.67/3

X=1.22

2(2-Y)-Y=9

4-2Y-Y=9

-3Y=9-4

-3Y=5

-Y=5/3

Y=-1.67

A. 3X+(-1.67)=2

3X-1.67=2

3X=2+1.67

3X=3.67

X=3.67/3

X=1.22

Nov 05, 2007 | SoftMath Algebrator - Algebra Homework...

408 people viewed this question

Usually answered in minutes!

×